2019
DOI: 10.14455/isec.res.2019.12
|View full text |Cite
|
Sign up to set email alerts
|

Amass: Advanced Manufacturing for the Assembly of Structural Steel

Abstract: This paper describes a collaborative project between the US, Ireland, and Northern Ireland (UK) to investigate advanced manufacturing cutting techniques for the creation of a new class of intermeshed steel connections that rely on neither welding nor bolting. To date, advanced manufacturing equipment has only been used to accelerate traditional processes for cutting sheet metal or other conventional fabrication activities. Such approaches have not capitalized on the equipment's full potential. This project lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…For example, the construction industry is one of the most injury-prone industries, in which production is usually prioritised over safety performance in daily on-site communications (Kines et al, 2010;Edwards et al, 2019Edwards et al, , 2020. In addition, without relying solely on structural steel connection systems such as field welding and bolting (being high risk, time-consuming and/or expensive) to assemble a connection in the field, the simplicity and efficiency of the steel process industry may be significantly improved (Schultz et al, 2019). It can be concluded that the availability of a good standard method of working is regarded as being equally important as the improvement of the standards, whereby the alignment of activities is facilitated by the direction given by top management (De Lange-Ros, 1999).…”
Section: Visualisation Of Similarities Viewer Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the construction industry is one of the most injury-prone industries, in which production is usually prioritised over safety performance in daily on-site communications (Kines et al, 2010;Edwards et al, 2019Edwards et al, , 2020. In addition, without relying solely on structural steel connection systems such as field welding and bolting (being high risk, time-consuming and/or expensive) to assemble a connection in the field, the simplicity and efficiency of the steel process industry may be significantly improved (Schultz et al, 2019). It can be concluded that the availability of a good standard method of working is regarded as being equally important as the improvement of the standards, whereby the alignment of activities is facilitated by the direction given by top management (De Lange-Ros, 1999).…”
Section: Visualisation Of Similarities Viewer Findingsmentioning
confidence: 99%
“…A growing body of literature aims at understanding environmental and ecological motives, reshaping entire trajectories of technological innovation and shifting away from the current technical-economic paradigm (Rynikiewicz, 2008). An example is the recent development of new universally applicable structural steel connection systems to achieve heightened material reuse within a circular economy (Schultz et al , 2019). With the increasing globalisation of trade, organisational, local and national cultures start to overlap (Bolton and Heap, 2002).…”
Section: Visualisation Of Similarities Viewer Findingsmentioning
confidence: 99%
“…This limit is controlled by the slightly reduced flange width due to the cutting of the fingers. More details on the connection load path and load transfer are available in [15], [16].…”
Section: Side Isc (Sisc)mentioning
confidence: 99%
“…Capitalizing on advances in digital manufacturing to accelerate on-site structural steel assembly and addressing some of the disassembly issues, a new concept in gravity-resisting steel connections entitled the intermeshed steel connection (ISC), is proposed herein; a brief description of the concept was previously presented as a conference paper [25]. The fundamental concept of the ISC is to replace existing field connections with those that are easier and faster to assemble.…”
Section: Intermeshed Steel Connection (Isc)mentioning
confidence: 99%